2015
DOI: 10.5007/2175-7968.2015v35nesp2p17
|View full text |Cite
|
Sign up to set email alerts
|

Os estudos da tradução e da interpretação de línguas de sinais: novo campo disciplinar emergente?

Abstract: Resumo: Considerando que as pesquisas brasileiras sobre a tradução e a interpretação de/para/entre línguas de sinais podem ser reunidas sobre o que se apresenta como Estudos da Tradução e da Interpretação de Línguas de Sinais (ETILS), realizamos uma reflexão sobre a emergência desse novo campo disciplinar em relação à sua vinculação direta aos Estudos da Tradução (ET) e aos Estudos da Interpretação (EI). Para tanto, apresentamos a interdependência e distinção fundamental entre os ET e os EI, realizamos uma bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Hence, it should be noted that such effects are neither finite nor fixed. Considerations by Santos (2015), Rodrigues and Beer (2015), and Dinarte and Russo (2015) point in that direction, as they discuss pertinent issues about the implementation of SLI activities at federal universities, affiliation to translation and interpretation studies, and SLI work in graduate programs, respectively. Finally, we should mention that these meaning effects came about at a given time in history and are always open to new analyses should production conditions change.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it should be noted that such effects are neither finite nor fixed. Considerations by Santos (2015), Rodrigues and Beer (2015), and Dinarte and Russo (2015) point in that direction, as they discuss pertinent issues about the implementation of SLI activities at federal universities, affiliation to translation and interpretation studies, and SLI work in graduate programs, respectively. Finally, we should mention that these meaning effects came about at a given time in history and are always open to new analyses should production conditions change.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, regarding intermodal translation, we have observed that there are some specificities related to its operationalization, since signed languages recorded on video are commonly employed as the final product of the translation of written or oral texts produced in spoken languages. Moreover, the translation of sign languages has been increasing significantly nowadays, especially within the academic environment, with its different directions and possibilities (Wurm 2010, Rodrigues, Beer 2015, Rigo 2015.…”
Section: Final Considerationsmentioning
confidence: 99%
“…Além disso, muitas pesquisas têm sido realizadas e têm se filiado ao campo dos Estudos da Tradução e Interpretação (cf. SANTOS, 2013, RODRIGUES & BEER, 2015, o que tem contribuído para se pensar ainda mais nas questões inerentes à prática desses profissionais.…”
unclassified